The Adsorption of Zn(II) Ions onto Chitin: Determination of Equilibrium, Kinetic and Thermodynamic Parameters - Kocer, N. Nacer; Uslu, G.; Cuci, Y. (Sage Publications Inc, 2008)
The adsorption of zinc(II) ions from aqueous solutions onto chitin was investigated as a function of the initial pH, temperature and initial metal ion concentration of the solutions concerned. The highest Zn(II) ion adsorption capacity was determined as 8.21 mg/g for an initial Zn(II) ion concentration of 300 mg/l at a pH value of 4.5 at 40 degrees C. The Freundlich and Langmuir adsorption models were used for the mathematical description of the adsorption equilibrium and isotherm constants were evaluated at different temperatures. The adsorption data were well described by the Langmuir equation although they could also be modelled by the Freundlich equation. The thermodynamics constants Delta G(0), Delta H-0 and Delta S-0 for the adsorption process were evaluated as -19.73 kJ/mol (at 40 degrees C), 4.13 kJ/mol and 0.076 kJ/(mol K), respectively. These values show that the adsorption of Zn(H) ions onto chitin was both endothermic and spontaneous.
Keywords: Industrial-Waste-Water; Aqueous-Solutions; Heavy-Metal; Biosorption; Removal; Sorption; Copper(Ii); Lead(Ii); Model; Cu2+